If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6.5(4p + 6) + -1.4(3p + -5) = 0 Reorder the terms: -6.5(6 + 4p) + -1.4(3p + -5) = 0 (6 * -6.5 + 4p * -6.5) + -1.4(3p + -5) = 0 (-39 + -26p) + -1.4(3p + -5) = 0 Reorder the terms: -39 + -26p + -1.4(-5 + 3p) = 0 -39 + -26p + (-5 * -1.4 + 3p * -1.4) = 0 -39 + -26p + (7 + -4.2p) = 0 Reorder the terms: -39 + 7 + -26p + -4.2p = 0 Combine like terms: -39 + 7 = -32 -32 + -26p + -4.2p = 0 Combine like terms: -26p + -4.2p = -30.2p -32 + -30.2p = 0 Solving -32 + -30.2p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + -30.2p = 0 + 32 Combine like terms: -32 + 32 = 0 0 + -30.2p = 0 + 32 -30.2p = 0 + 32 Combine like terms: 0 + 32 = 32 -30.2p = 32 Divide each side by '-30.2'. p = -1.059602649 Simplifying p = -1.059602649
| 50+4y-22=13y-14-3y | | (31/4)p=21/2 | | 1/5n=12 | | -3-(5-5p)=0 | | -3(-2*x+4)-(x-6)=y | | f(m)=20-0.25m | | 69-5x=4x+18 | | 3y-10=5x+22 | | x^2=-13 | | -17x-20=-14x+70 | | -7/3(y-12)-1/6y=0 | | 3/4x-3/2=6 | | -7/3(y-12)-1/6y | | 4x+9=3x+17 | | 3x+7=2x+15 | | 5x^3/2-35=100 | | -177=9*n | | 11x-3=3x+21 | | 9x+18=27 | | 5x-35=100 | | 6x-5=31-2x | | 24-3x=56+2x | | 3x-4(7x+3)=5x+7(9x-10) | | 5.59+55.9=111.8 | | -17-(-40)=x/2 | | X=2(-2)+6 | | X*13-110=x*6-12 | | 5(5c-1)-3=23c+2 | | 3x/2+5=16x-11 | | 8w=4.2 | | 2/5n=24 | | 5-8x=92-29x |